The gendered effects of family migration law: contextual interpretation as a possible judicial remedy - Staiano, Fulvia (Investigaciones Feministas (Feminist Research), 2016)
At all normative levels, family migration law can disproportionally and negatively affect immigrant women’s rights in this field, producing gendered effects. In some cases, such effects are related to the normative and judicial imposition of unviable family-related models (e.g., the ʻgood mother ̕ the one-breadwinner family, or a rigid distinction between productive and reproductive work). In other cases, they are due to family migration law’s overlooking of the specific needs and difficulties of immigrant women, within their families and in the broader context of their host countries’ social and normative framework. To effectively expose and correct this gender bias, in this article I propose an alternative view of immigrant women’s right to family life, as a cluster of rights and entitlements rather than as a mono-dimensional right. As a theoretical approach, this construction is better equipped to capture the complex experiences of immigrant women in the European legal space, and to shed light on the gendered effects generated not by individual norms but by the interaction of norms that are traditionally assigned to separated legal domains (e.g., immigration law and criminal law). As a judicial strategy, this understanding is capable of prompting a consideration by domestic and supranational courts of immigrant women not as isolated individuals, but as ‘individuals in context’. I shall define this type of approach as ‘contextual interpretation’, understood as the consideration of immigrant women in the broader contexts of their families, their host societies and the normative frameworks applicable to them. Performed in a gendersensitive manner, a contextual judicial interpretation has the potential to neutralize the gendered effects of certain family migration norms. To illustrate these points, I will discuss selected judicial examples offered by the European Court on Human Rights, as well as from domestic jurisdictions of countries with a particularly high incidence of immigrant women (Italy and Spain).